Distribution of Al in Al–Si Alloys during electromagnetic continuous casting with cylindrical open ended crucible. (3rd September 2015) - Bai, X.; Li, J.; Fu, Z.; Li, Y.; Ban, B.; Zhang, T.; Peng, Z.; Wang, C.; Chen, J.
Abstract : Electromagnetic continuous casting (EMCC) exhibits great potential for silicon purification by Al–Si method. Distribution of Al in Al–Si alloys with different aluminium contents during EMCC was investigated. The macrostructure of the Al–Si alloy ingots reveals that the content of primary silicon plates in hypereutectic alloys decreases from the bottom to the top of the ingots, and no obvious primary silicon plate exists in eutectic alloy. The fitting results of aluminium distribution in the alloys reveal two types of aluminium distribution patterns in hypereutectic Al–Si alloys: Scheil model for high temperature solidification and initial transient model for low temperature one. An apparent segregation coefficient of Al is proposed to characterise the solidification process, which is ∼0.83 in the hypereutectic alloys.